Accessing Education: Equity, Diversity, and Inclusion in Online Learning - Ikebuchi, Shelly (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2023)
As Canadian post-secondary institutions emerge from the pandemic restrictions, they are in a historically unique position to assess how online education has both facilitated and hindered learning, and how the effects might be greater for some. In this study, open-ended comments from the Canadian Digital Learning Research Association 2022 Spring National Survey were analyzed to understand how online and/or hybrid learning both supported equity, diversity, and inclusion (EDI) and presented EDI-related challenges. The findings were that: (a) online and hybrid learning presents challenges of access for students marginalized by “race,” class, and location; (b) online and hybrid learning supports EDI by increasing access and flexibility; (c) pedagogy and course design are central to ensuring that online and/or hybrid learning supports EDI; and (d) student experiences and expectations around online learning indicate a need for support and flexibility. These findings highlight some of the promises of online and hybrid learning, but they also bring to light some of the challenges. This paper discusses three challenges, access, pedagogy, and technology, as well as flexibility, and recommendations that might begin to address EDI.